Damage effects of Au&He dual ion irradiated silicon carbide. (22nd August 2018) - Wang, Xu; Zhao, Ziqiang; Zhang, Ming; Zhao, Yunbiao; Han, Dong; Chu, Jian; Sun, Yaping; Wang, Honglong; Liu, Sunli
Abstract: Synergistic effects of Au and He dual ion beam irradiations were investigated by comparing the damage accumulated in single crystalline silicon carbide (SiC). By implanting Au ions at 600 K and He ions at room temperature into 6H-SiC, the resulting damage was characterized using several advanced techniques, including Raman spectroscopy, Rutherford backscattering spectrometry in channeling mode (RBS/C), nano-indentation and high-resolution x-ray diffraction (HRXRD). Here, we report the complex effects induced by dual ion beam irradiations and we also investigate the isothermal annealing effects on dual ion irradiation damage. Synergy effects of Au and He dual irradiations have been observed. Irradiation damage produced by Au&He ions is larger than single ion irradiation. The displacement damage induced by heavy recoil atoms and helium atoms interact with each other, causing more serious damage. Interestingly, Au + He successive irradiation induced a larger damage level than He + Au successive irradiation, probably due to thermal annealing effect during Au irradiation. Finally, the hardness and Young's modulus of irradiated SiC were found to be highly related with single or dual ion irradiations, implantation sequences and the corresponding fluences.